Labor Conditions, Wages and Non-Cash Transfers in Poverty in Eastern Indonesia - Sihotang, Alim; Marselina; Arivina Ratih (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Poverty is a complex and prolonged problem because it touches all aspects of both social, economic and Environmental Society at large. The Eastern region of Indonesia still has a high percentage of poverty, there are 5 provinces with a predominance of poverty percentage identified as being at a high percentage of poor population, including Papua 27.33%, West Papua 22.67%, East Nusa Tenggara 21.10%, Maluku 17.74% and Gorontalo 16.17%. This study identifies the factors of productivity components of the poor with the variable influence of non-cash direct assistance, minimum wage and informal sector workers on poverty cases in 5 regions of eastern Indonesia. This study uses Panel Data with the ordinary Least Squaremethod, this researcher in the period 2016-2022 by using regional observation or (cross section) 5 provinces in eastern Indonesia including Maluku, Gorontalo, East Nusa Tenggara, Papua and West Papua. Informal sector workers (PSI) have a positive and significant effect, the Minimum wage (UM) has a negative and significant effect and non-cash food assistance (BPNT) has no effect on poverty in 5 provinces in eastern Indonesia in 2016-2022.